2021
DOI: 10.4995/muse.2021.14875
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Analysis of Art Teachers’ Use of Transmedia Technology

Abstract: <p>Transmedia technology is a modern innovative system which scientists consider to be real communication revolution. Transmedia technology is investigated and actively implemented in different life spheres and social activities, such as mass media, journalism, marketing, culture, education etc. There is an urgent need to study the opportunities of using the transmedia technologies in art education, in particular in music teachers’ professional training. The implementing of transmedia technology in music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…These conclusions prop up the research findings by Kapalygina (2021) and Almashi(2019),which expose that the integration of ICTs fosters the construction of social behavior on digitalization. These findings support the results of a study by Havrilova, et al (2021), which maintained that implementing ICTs is a novel strategy, that researchers consider the turning point of modern communication. This also confirms the findings of research by Alvarado et al (2020), which maintained positive attitudes and psychological readiness of teachers towards technology was of paramount importance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These conclusions prop up the research findings by Kapalygina (2021) and Almashi(2019),which expose that the integration of ICTs fosters the construction of social behavior on digitalization. These findings support the results of a study by Havrilova, et al (2021), which maintained that implementing ICTs is a novel strategy, that researchers consider the turning point of modern communication. This also confirms the findings of research by Alvarado et al (2020), which maintained positive attitudes and psychological readiness of teachers towards technology was of paramount importance.…”
Section: Discussionsupporting
confidence: 88%
“…It is significant to highlight the importance of developing the digital proficiencies of students in the new horizon of technologies. Trans-media technology, in this perspective, as described by Havrilova, Oriekhova, Beskorsa, Churikova-Kushnir, and Sofronii,(2021) is a recent inventive plan, which scientists deem the actual communication revolt. Letendre(2017), in this perspective, put ICT in the concept of world culture and educational psychology.…”
Section: Towards a Technology Shift: Major Merits And Challengesmentioning
confidence: 99%
“…In our study, the determination of the main directions of psychological preparation for pedagogical innovations showed that psychological preparation for pedagogical innovations is determined by various factors. According to the researchers, the application of transmedia technology in the psychological preparation of teachers for pedagogical innovations contributes to the qualitative development of their professional competence, the expansion of their worldview, and the improvement of their professional skills (Havrilova, 2021). At the same time, many researchers believe that one of the most important aspects leading to innovation is the use of information and communication technologies by teachers in the classroom (Ibieta, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of network technology and its wide application in art education, it also provides great help to multimedia art education (Tang, 2021). The development of network technology makes it more convenient for students to collect materials and receive art edification (Havrilova et al,2021). It provides the possibility for students to choose content from a large number of materials, so that students with different ideas and abilities can obtain information and materials by themselves and interact with others, so as to improve their analysis and induction of art works.…”
mentioning
confidence: 99%